Are the impacts of carbon nanotubes or increased temperature enhanced in Mytilus galloprovincialis submitted to air exposure? - Andrade, Maria Madalena da Silva (2018)
Intertidal species are frequently exposed to environmental changes associated with multiple stressors to which they must avoid or tolerate by developing certain strategies. Some of the natural environmental changes are correlated with the tidal cycle which forces organisms to tolerate the differences between an aquatic and an aerial environment. Apart of these differences, intertidal mussels are also subjected to global warming and consequently, the risk of desiccation especially under aerial environment. Furthermore, pollutants exposure from anthropogenic sources is another daily stress that organisms must cope with it. The present study evaluated the impacts in Mytilus galloprovincialis exposed to different temperatures (18ºC and 21ºC) or carbon nanoparticles (0.01 mg/L MWCNT) when continuously submersed or exposed to tides (5 h of low tide, 7 h of high tide) for 14 days. Results evidenced that mussels were physiological and biochemical affected by increased temperature or MWCNTs exposure, especially when exposed to tides. When only exposed to increased temperature, the stress induced was enough to activate mussels’ antioxidant defenses by spending energy reserves and avoid oxidative damage. When only exposed to MWCNTs or only exposed to tides, the stress induced was not enough to activate mussels’ antioxidant defenses which resulted in oxidative damage. Nevertheless, the combination of tides and temperature, resulted into high production of reactive oxygen species (ROS), which lead to a significant decrease of lipids (LIP) content, activation of antioxidant defenses (superoxide dismutase, SOD and glutathione peroxide, GPx) and increase of oxidized glutathione (GSSG), yet organisms couldn’t prevent cellular damage, showing an increase of lipid peroxidation (LPO). Therefore, the combination of increased temperature and air exposure during ebb tides demonstrated to induce higher oxidative stress. Similarly, when mussels were exposed to the combination of tides and MWCNTs, resulted into high production of reactive oxygen species (ROS), associated with an increase of metabolism, which lead to a significant increase of antioxidant defenses (superoxide dismutase, SOD and glutathione peroxide, GPx) and oxidized glutathione (GSSG), and thus organisms were able to prevent cellular damage, showing no lipid peroxidation (LPO) or protein carbonylation (PC) levels. Therefore, organisms seemed to be able to tolerate MWCNTS and air exposure during ebb tides, however the combination of both stressors demonstrated to induce higher oxidative stress. These findings indicate that the increasing global warming and the increasing presence of carbon nanoparticles in marine ecosystems can induce sub-lethal and higher toxic impacts, respectively, in intertidal organisms compared to organisms continuously submersed in marine ecosystems. Furthermore, our results may indicate that air exposure can act as a cofounding factor on the assessment of different stressors in organisms living in coastal systems